2012
DOI: 10.1353/sls.2012.0001
|View full text |Cite
|
Sign up to set email alerts
|

Word Order in Russian Sign Language

Abstract: In this paper the results of an investigation of word order in Russian Sign Language (RSL) are presented. A small corpus of narratives based on comic strips by nine native signers was analyzed and a picturedescription experiment (based on Volterra et al. 1984) was conducted with six native signers. The results are the following: the most frequent word order in RSL is SVO for plain and agreeing verbs and SOV for classifier predicates. Some factors can influence the word order, namely aspect marking on the verb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 12 publications
7
42
0
1
Order By: Relevance
“…Emmorey 2003). This observation corresponds to the cross-linguistic pattern described in Padden (1988), Kegl (2004), Milković et al (2006), Hendriks (2008) and Kimmelman (2012), among others. Interestingly, the semantic feature of animacy seems to be an important factor too.…”
Section: Resultssupporting
confidence: 84%
“…Emmorey 2003). This observation corresponds to the cross-linguistic pattern described in Padden (1988), Kegl (2004), Milković et al (2006), Hendriks (2008) and Kimmelman (2012), among others. Interestingly, the semantic feature of animacy seems to be an important factor too.…”
Section: Resultssupporting
confidence: 84%
“…For the languages that favor SVO with plain verbs in reversible sentences, it would seem that NP 1 V NP 2 order is not ambiguous (interpreted only as SVO), whereas NP 1 NP 2 V order is open to the readings SOV and OSV (and see Fischer, 1975 ). In contrast, Kimmelman ( 2012 ) points out for Russian Sign Language, that, since OSV is marked, the cues that go with topicalization of the O should eliminate ambiguity in reversible sentences. The observation captured in generalization six remains, and we return to discussion of possible motivation in sections An Amodal Account and A Modal Account.…”
Section: Generalizations In the Datamentioning
confidence: 96%
“…Here we see a V sandwich from Russian Sign Language where the second instance of the V is accompanied by a non-manual adverbial morpheme (Kimmelman, 2012 , example 47):…”
Section: Generalizations In the Datamentioning
confidence: 99%
“…Additional evidence that SOV and SVO word orders are overwhelmingly preferred comes from several other sources. First, Kimmelman (forthcoming) found that in a sample of 24 sign languages, 21 (88%) have SOV and/or SVO as the dominant sequencing pattern(s). Second, within the last 70 years, Al‐Sayyid Bedouin Sign Language (ABSL) has gradually arisen in an isolated community with a high incidence of genetically based prelingual deafness, and in the space of a single generation, it assumed a grammatical structure characterized by SOV order (Sandler et al.…”
Section: The Cross‐linguistic Prevalence Of Sov and Svo Word Ordersmentioning
confidence: 99%